A first principles study of the surface electronic properties of Mo2C. (15th September 2022) - Xu, Hua; Cen, Weifu; Tian, Zean; Zheng, Quan; Gao, Tinghong; Liang, Yongchao; Xie, Quan
Abstract: The electronic structure and optical properties of Mo2 C with different surface atomic layer thicknesses (SALTs) have been investigated by employing the plane wave ultra-soft pseudopotential method based on the first principles. It is found that the LDA density generalization approximation is most suitable for the optimization of the geometry of Mo2 C, under which the lowest energy and most stable structure are obtained. As the SALT decreases, the hybridization of Mo-d and Mo-p electrons in the valence band forms strongly hybridized orbitals. It suppresses the photoelectron leap of and increases the band gap, allowing the conversion of Mo2 C from metal to semiconductor. Therefore, the dielectric function, refractive index, reflection spectrum, and absorption spectrum can be improved by adjusting the SALT of Mo2 C. These findings can provide a theoretical basis for improving and optimizing its photoelectronic properties. Highlights: The LDA density generalization approximation is most suitable for the optimization of the geometry of Mo2 C. The transformation of Mo2 C from metallic to semiconductor properties was achieved by adjusting SALT. Different SALT can effectively modulate the optical properties of Mo2 C, increase the optical utilization.